2017
DOI: 10.17564/2316-3801.2017v5n3p69-84
|View full text |Cite
|
Sign up to set email alerts
|

Estudo Da Correlação Entre O Índice De Desenvolvimento Humano (Idh) E Os Tributos Arrecadados Nos Estados Brasileiros

Abstract: The subject of study in this article is the relationship between human development, represented by the HDI, and the amounts of tax collected in each Federal State of Brazil, considering the taxes in the three spheres of government, namely the Union, the States and the Municipalities. The research utilized data available on the websites of the National Treasury, Federal Revenue, IBGE and Atlas Brazil in 2013 to build a statistical model correlating the HDI value with the total tax collected per capita of each s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
3
0
1
Order By: Relevance
“…This result is based on the three pillars that constitute the HDI: health (long, healthy life measured by life expectancy at birth); education (access to information measured by composite indicators of education of the adult population and the school flow of young population); and income (life standard measured by the per capita income) (PNUD, 2010). Braga et al (2017) found a correlation between HDI and municipal tax revenue for the presence of public policies related to economic development, health, and education.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…This result is based on the three pillars that constitute the HDI: health (long, healthy life measured by life expectancy at birth); education (access to information measured by composite indicators of education of the adult population and the school flow of young population); and income (life standard measured by the per capita income) (PNUD, 2010). Braga et al (2017) found a correlation between HDI and municipal tax revenue for the presence of public policies related to economic development, health, and education.…”
Section: Resultsmentioning
confidence: 93%
“…The GINI index, which measures the degree of concentration of income among social classes, also varies from zero to one; but, the closer to zero, the better the income distribution. Moreover, the municipal tax revenue is not always readily available by municipal managers for public actions (BRAGA et al, 2017). In addition, some municipalities have financial/budgetary problems that affect even the maintenance of basic public services, such as health, education, safety, and the salary of public employees.…”
Section: Resultsmentioning
confidence: 99%
“…The HDI is considered an average for summarizing the basic conditions of a population, focusing on education, income, and quality of life. Published in Brazil for the first time in the year 1990, the HDI has gradually become a reference in several places around the world (Braga, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Na busca por resposta a esta questão, as administrações públicas passaram a empregar indicadores sociais no planejamento de suas atividades com o intuito de subsidiar a definição de prioridades para a alocação dos recursos públicos (JANNUZZI, 2002;ÁVILA;BITTENCOURT, 2017). Dentre os principais indicadores destaca-se o Índice de Desenvolvimento Humano (IDH), que sintetiza o grau de desenvolvimento de um país ou região, por cálculos relacionados à saúde, educação e renda, entendidos como direitos humanos em muitos lugares do mundo (ÁVILA; BITTENCOURT, 2017;BRAGA et al, 2017).…”
Section: Introductionunclassified